Using Quizizz in Improving Students’ English Learning Outcomes of Narrative Text - Loga Nurmantara; Sri Susanti; Eryansyah Eryansyah (IAIN Syekh Nurjati Cirebon, 2023)
This research is a Classroom Action Research aims to improve English learning outcomes on Narrative Text material for students in class X.6 which amounted to 32 people at SMAN 11 Palembang. This research activity aims to help improve knowledge and develop skills in the selection of learning media so as to improve student learning outcomes, in order to support the improvement of the quality of education and the quality of graduates at SMA Negeri 11 Palembang. This research was conducted in two cycles and used data such as observation and Pre-Test and Post-Test. The average score obtained by students in the first cycle was 50 with a percentage of Learning Objective Completeness Criteria of 28.12% which was still below the desired percentage of 80%. While the average value of cycle 2 was obtained 81 with a percentage of 81.25% which was categorized as